Pilot Study of Reproductive Health Counseling in a Pediatric Rheumatology Clinic. Issue 4 (April 2014) - Ronis, Tova; Frankovich, Jennifer; Yen, Sophia; Sandborg, Christy; Chira, Peter
<x xml:space="preserve">Abstract</x> Objective To assess perception and behavior after reproductive health counseling among adolescent patients in a tertiary care–based pediatric rheumatology clinic. Methods Adolescent females seen at a Stanford pediatric rheumatology clinic were prospectively enrolled during routine visits. At the study start, standard clinic procedures were reviewed with providers for the following: 1) the home, education, activities, drugs, sexual activity, and suicide/depression (HEADSS) assessment; 2) reproductive health counseling; and 3) medical record documentation. Patients were enrolled if providers indicated that they performed the HEADSS assessment and reproductive health counseling. At enrollment, patients completed a survey to assess their perceptions of reproductive health counseling. Chart reviews confirmed documented discussions. A followup survey performed 3–5 months after enrollment tracked reproductive health information–seeking behavior. Results In total, 90 females (mean ± SD age 17 ± 2 years) participated. Almost all patients (99%) agreed that reproductive health was discussed; 71% reported that pregnancy risks were discussed, 42% had recent concerns about reproductive health, and 33% reported their provider recommended that they seek further reproductive health care. Eighty‐four patients completed followup phone surveys, with 25% reporting seeking further information on reproductive health concerns, but with only 9.5% actually seeking further care. Only 18% of patients reported having ever asked their rheumatology provider for guidance regarding reproductive health care concerns. Conclusion Routine reproductive health discussion and counseling are necessary in a rheumatology clinic because, in our experience, a substantial number of adolescents have concerns and actively seek reproductive health information. Despite these discussions, adolescents rarely pursue further reproductive health care. Further work to bridge this gap is needed.